Viticulture of Hungary - Hajdu, Edit (Acta Agraria Debreceniensis, 2018)
For several thousand years, vine has been grown in the Carpathian basin, where the climatic and soil conditions are favourable for viticulture. During this long period, vine growing has been developing until it reached its current niveau. We grow propagation material, table grape and wine grape. The produced wine grape varieties are grown on the largest area, of which 72% is white wine and 25% is red wine. Only 3% remains for table grapes. The surface of vineyards is about 63 000 ha, which can be found in 22 wine regions. The biodiversity of vine is very rich in our country. There are a lot of native and valuable bred varieties and clones in cultivation. The resistant and winter frost resistant vine varieties have an important role in our continental climate. The in 75% of the vineyards is on hills and mountains, 25% of them is on the Great Hungarian Plain. High cordon with cane pruning dominates the training and pruning system.Unfortunately, vine stocks suffer from a lot of diseases and by using pesticides we pollute the nature. Viticulturists in Hungary produce excellent raw material and provide oenologists with them who make wine of excellent quality.